2016
DOI: 10.1097/md.0000000000004336
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical significance of nonorgan specific antibodies in patients with autoimmune thyroiditis as predictor markers for rheumatic diseases

Abstract: Autoimmune diseases are considered the 3rd leading cause of morbidity and mortality in the industrialized countries. Autoimmune thyroid diseases (ATDs) are associated with high prevalence of nonorgan-specific autoantibodies, such as antinuclear antibodies (ANA), antidouble-stranded deoxyribonucleic acid (anti-dsDNA), antiextractable-nuclear antigens (anti-ENAs), rheumatoid factor (RF), and anticyclic-citrullinated peptides (anti-CCP) whose clinical significance is unknown.We aimed to assess the prevalence of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 27 publications
0
18
1
2
Order By: Relevance
“…However, this was a study with a different design from the present study, as these authors did not exclude patients with prior diagnosis of rheumatic disease from their sample. In contrast to our findings, Elnady et al [13] followed HT patients with non-organ specific autoantibodies for 2 years and found that almost 1/3 developed rheumatic disease; anti-dsDNA and RF were the most significant predictors of disease occurrence. Differences in the ethnic background of the studied sample may explain some of these discrepancies as both ATD and rheumatic diseases are influenced by genes such as MHC class 2, CTLA4, and PTPN22 [16].…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…However, this was a study with a different design from the present study, as these authors did not exclude patients with prior diagnosis of rheumatic disease from their sample. In contrast to our findings, Elnady et al [13] followed HT patients with non-organ specific autoantibodies for 2 years and found that almost 1/3 developed rheumatic disease; anti-dsDNA and RF were the most significant predictors of disease occurrence. Differences in the ethnic background of the studied sample may explain some of these discrepancies as both ATD and rheumatic diseases are influenced by genes such as MHC class 2, CTLA4, and PTPN22 [16].…”
Section: Discussioncontrasting
confidence: 52%
“…On the contrary, in the other half of ANA-positive patients the pattern was fine or coarse speckled and about 15% of them were positive for anti-Ro/SS-A. Morita et al [11] did not find anti-Ro/SS-A in their 50 patients with autoimmune thyroid disease, but Tektonidou et al [12] found a prevalence of 10% of anti-Ro/SS-A positivity, and Elnady et al [13], a positivity of 14.8% in their sample. Finding of anti-Ro/SS-A positivity in a disease with female predominance is very important, as this autoantibody may cross the placenta barrier in pregnant women and cause neonatal lupus with a risk of congenital heart block, independently of the diagnosis of a background disease [14].…”
Section: Discussionmentioning
confidence: 95%
“…These could form a link between AITD and rheumatoid arthritis and the impact of these two autoimmune diseases on bone quality. 30 Accumulating evidence suggests that osteoclasts, originating from the monocyte lineage and immune cells share a number of regulatory molecules including cytokines, receptors, signaling molecules and transcription factors, thereby mutually influencing each other. Furthermore, immune cells are derived from bone marrow and thus develop in the same microenvironment as osteoclasts.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the adverse effects of ARDs on pregnancy outcomes can be mediated by their association with thyroid autoimmunity. In particular, subjects with ARDs have an increased prevalence of antithyroid antibodies in both pregnant and non‐pregnant states . In addition, the detection of isolated antithyroid antibodies is a risk factor for the subsequent development of a rheumatic disorder .…”
Section: Biological Basis Of Adverse Pregnancy Outcomesmentioning
confidence: 99%